Cerebral Angiogenesis Methods and Protocols - Milner, Richard; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2014)
Providing a selection of the key techniques that are used in characterizing cerebral angiogenesis, Cerebral Angiogenesis: Methods and Protocols aims to define the cellular and molecular mechanisms underlying this important process.  Divided into six parts, this detailed volume examines cerebral angiogenesis occurring in different scenarios, a variety of different models in which cerebral angiogenesis can be studied, methods to characterize and quantify angiogenic events as well as several different approaches to measure changes in cerebral blood flow, different approaches to investigate the role of specific candidate genes in cerebral angiogenesis, methods of therapeutically manipulating cerebral angiogenesis by gene delivery, and finally important approaches to examine cerebral angiogenic mechanisms in vitro.  Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their specific topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Comprehensive and decidedly practical, Cerebral Angiogenesis: Methods and Protocols should be a vital resource for all researchers, both those new to this field as well as those looking to use more specialized and sophisticated techniques to examine blood vessel growth in the brain.
Cerebral Angiogenesis During Development: Who’s Conducting the Orchestra? -- Cerebral Angiogenesis: A Realistic Therapy for Ischemic Disease? -- Vascular Normalization in Cerebral Angiogenesis: Friend or Foe? -- Pericytes and Adaptive Angioplasticity: The Role of Tumor Necrosis Factor Weak Inducer of Apoptosis (TWEAK) -- Analysis of Angiogenesis in the Developing Mouse Central Nervous System -- Hypoxia-Induced Angiogenesis and Capillary Density Determination -- The Middle Cerebral Artery Occlusion Model of Transient Focal Cerebral Ischemia -- A Mouse Model of Chronic Cerebral Hypoperfusion Characterizing Features of Vascular Cognitive Impairment -- A Mouse Model of Permanent Focal Ischemia: Distal Middle Cerebral Artery Occlusion -- A Method of Inducing Global Cerebral Ischemia -- Induction of Cerebral Arteriogenesis in Mice -- Vessel Painting Technique for Visualizing the Cerebral Vascular Architecture of the Mouse -- Examining Cerebral Angiogenesis in Response to Physical Exercise -- Histological Assessment of Angiogenesis in the Hypoxic Central Nervous System -- Examining Vascular Remodeling in the Hypoxic Central Nervous System -- Analysis of Cerebral Angiogenesis in Human Glioblastomas -- Quantitative Cerebral Blood Flow Measurements Using MRI -- Fluorescent Angiogenesis Models Using Gelfoam® Implanted in Transgenic Mice Expressing Fluorescent Proteins -- Laser Speckle Contrast Imaging to Measure Changes in Cerebral Blood Flow -- Laser Doppler Flowmetry to Measure Changes in Cerebral Blood Flow -- Defining the Role Of HIF and Its Downstream Mediators in Hypoxic-Induced Cerebral Angiogenesis -- Inducible Gene Deletion in Glial Cells to Study Angiogenesis in the Central Nervous System -- Bone Marrow Chimera Experiments to Determine the Contribution of Hematopoietic Stem Cells to Cerebral Angiogenesis -- Novel Methods for Accurate Identification, Isolation, and Genomic Analysis of Symptomatic Micro-Environments in Atherosclerotic Arteries -- Induction of Brain Arteriovenous Malformation in the Adult Mouse -- Stimulation of Cerebral Angiogenesis by Gene Delivery -- Investigating the Role of Perlecan Domain V in Post-Ischemic Cerebral Angiogenesis -- Isolation and Culture of Primary Mouse Brain Endothelial Cells -- Purification of Endothelial Cells from the Rat Brain -- Generation of Primary Cultures of Bovine Brain Endothelial Cells and Setup of Co-Cultures with Rat Astrocytes -- Isolation and Culture of Primary Pericytes from Mouse Brain -- Assays to Examine Endothelial Cell Migration, Tube Formation, and Gene Expression Profiles -- A Neurovascular Blood-Brain Barrier In Vitro Model -- In Vitro Models of the Blood-Brain Barrier.
Keywords: Neurosciences; Neurobiology; Neurosciences; Neurobiology